A Economia Política do Sacro-Império Romano: Uma Investigação Histórica - Coelho, Sávio (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
The Holy Roman Empire was a state that existed in Central Europe between 800 and 1806 A.D. Unlike modern european states, the Holy Roman Empire was a political struture highly fragmented into varied semi-independent units, from principalities to city states. In this article it will be explored, as a historical case of the I German Reich, with its decentralized principalities, provides a practicle example of a radical federalist system and a proprietarian monarchy as theorized in Hoppe (2017). In addition, it will be approached with the context it has been analyzed and justified by the administrative doctrine of german cameralism.